Effectiveness of Islamic Spiritual Therapy on the Feeling of Loneliness and Death Anxiety in Elderly People - Zahra Dashtbozorgi (روانشناسی پیری, 2016)
Spirituality as the foundation of beliefs is an important aspect of elderly people’s life and has a basic role in providing and promoting their psychological health and life quality. Therefore, the present research was conducted to evaluate effectiveness of Islamic spiritual therapy on loneliness and death anxiety in elderly people’s life. The research was semi-experimental with pre-test, post-test with control group. The statistical population of the research included all elderly women in Ahwaz. Among elderly women in Ahwaz, as available 30 individuals were selected who had obtained a score equal to or higher than cutting point in loneliness questionnaire of Dehshiri et al and death anxiety questionnaire of Kult Leicester and were replaced randomly in two groups of experiment (15 people) and control (15 people). Then a plan of training spirituality based on Islamic lessons was implemented for the experiment group in 12 sessions for 30 minutes and during this period the control group received no intervention. After the end of the training plan, questionnaires were implemented again for both groups in the form of posttest. Data was analyzed and evaluated through multivariate covariance test. Results indicated that training spirituality based on Islamic lessons has led to reduction in feeling of loneliness and death anxiety in the experiment group. As the result, making required grounds in order to participate in religious activities for elderly people seems necessary, in this case it can be effective in improvement of elderly people’s psychological status.